L'educazione permanente a partire dalle prime età della vita - Ulivieri, Simonetta (Educazione per tutta la vita - Open Access, 2016)
The volume presents the Acts of the SIPED International Conference "Permanent Education From the Early Ages of Life", in which the concept of education is explored as a process that continues throughout all the life and is built in several training environments.